In Search of a Strong Agenda: An Interview with Kenneth M. Curtis - Curtis, Kenneth (Maine Policy Review, 1992)
In an interview this fall with Maine Policy Review, Kenneth Curtis, the former governor, former chairman of the Democratic National Committee, and former U.S. ambassador to Canada, shared his insights into the civic and political life of Maine and the nation. Not surprisingly, Curtis, currently president of Maine Maritime Academy, argues that many attitudes about the ineffectiveness and the unresponsiveness of government could be overcome by strong leadership from the executives of federal and state governments. He asserts that federal and state chief executives need to offer a vision of the future, put forth strong political agendas, and then foster cooperation, not conflict, in implementing the goals and objectives of those agendas.
Keywords: Maine; state government; politics; civic engagement